IMPACT OF GALACTURONIC AND CITRIC ACID TREATMENTS ON THE PHYSICOCHEMICAL PARAMETERS AND SENSORY QUALITY OF TIGER NUT (Cyperus esculentus L.) MILK - Salihu, Ahmed; Vantsawa, Philip Anthony; Egbe, Nkechi Eucharia; Abdulsalami, Muhammed Sani; Dantata, Ashiru Muhammad (FUDMA Journal of Sciences, 2026)
The increasing demand for plant-based milk alternatives has driven interest in improving the quality and shelf life of tiger nut (Cyperus esculentus L.) milk. This study investigated the effects of citric and galacturonic acid treatments on the sensory attributes, pH, and reducing sugar content of tiger nut milk. Citric acid was extracted from ripe sweet oranges via ethanolic immersion and thermal agitation, whereas galacturonic acid was obtained through enzymatic hydrolysis of pectin using pectinase at 40°C for 2 hours. The acids were applied at varying concentrations (0.1–0.5 mg/ml), and the treated samples were evaluated over 120-hours. Sensory evaluation revealed moderate consumer preference, with 60–70% of   the panellists rating the colour, flavour, taste, aroma, and overall acceptability. Both acids significantly (p
Keywords: Tiger nut; Citric Acid; Galacturonic Acid; Sensory Properties; pH; Total Reducing Sugar